Flexible Supply Chain Design under Stochastic Catastrophic Risks - Yingjie Fan; Frank Schwartz; Stefan Voß (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Real-world experiences prove that supply chains may suffer great losses or even complete break downs after catastrophic events. However, extra costs after great disasters are usually not incorporated in the supply chain costs in the existing literature. The aim of this study is to design a flexible cost efficient supply chain, which is able to keep stable supply even if great disasters happen. The supply chain is designed by initially determining the location of production facilities and choosing a transportation mode for each transportation link, and then estimating extra costs after a catastrophe occurs according to the type of the catastrophe and the structure and transportation modes of the supply chain. All variable costs, including supply chain catastrophe costs, operational costs, holding costs and transportation costs are included in the objective function of a two stage stochastic decision model. An algorithm is used to solve the model in order to get an optimal or close to optimal structure of the supply chain. Numerical results are presented. Based on computational experiments we can deduce that postponement is effective to deal with supply chain catastrophic events; slow transportation seems a viable option to leave more time for a supply chain for the adjustment of production planning after catastrophes.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; supply chain risk management; slow transportation; postponement; catastrophe